Digital Policing and Public Trust in Zimbabwe: a Qualitative Case Study of Post- Covid 19 Pandemic Practices in Harare Metropolitan Province - Joshua Foma; Surya Nita; Brian Marambo; Sacrefise Cheuka (Riviera Publishing, 2026)
The swift digitalization of policing in Zimbabwe has altered law enforcement operations in the post-pandemic context; however, the impact on public trust is still unclear. This study examines the impact of digital policing initiatives by the Zimbabwe Republic Police (ZRP) on public perceptions of legitimacy and accountability, addressing an existing research gap. The main aim is to analyze significant digital policing practices adopted in Harare Metropolitan Province since the onset of COVID-19, evaluate their effects on public trust, and suggest policy strategies for an inclusive and ethical digital transformation. The study employs a qualitative case study design utilizing secondary data to apply the Technology Acceptance Model (TAM) and Social Capital Theory (SCT) in analyzing findings derived from government reports, academic literature, and media sources. The findings indicate that digital systems, including the Automated Fingerprint Identification System (AFIS), CCTV surveillance, and online reporting forums, have improved efficiency and communication; however, they have not significantly restored trust. Citizens perceive digital policing primarily as a mechanism of citizen control rather than empowerment, attributed to insufficient data governance, inadequate responsiveness, and lack of accountability mechanisms. The research indicates that technological modernization should be synchronized with transparency, ethical standards, and citizen engagement to enhance police legitimacy and public trust. The development of robust data protection policies, enhancement of ICT capacity, and promotion of participatory digital governance are recommended to ensure that innovation fosters public trust and democratic policing.